PENGEMBANGAN MEDIA PREPARAT JARINGAN TUMBUHAN MENGGUNAKAN PEWARNA ALTERNATIF DARI FILTRAT DAUN PACAR (Lawsonia inermis) - Ahmad, Sayyidah Nugrahani Nur (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
The objective of this research were to describe the validity plant tissue preparation media which is coloured using henna leaves filtrate as an alternative dye. The research procedures used is development research which includes three phases that are collective and plant determination phase, preparation media making phase, and preparation media research phase. The result of this research was plant tissue preparation media which is coloured using henna leaves as an alternatives dye it is chatagorized as valid and very valid, so can used as preparation media for observation plant tissue. Key words: The development of media, Plant tissue preparation, Alternative dye, Henna leave (Lawsonia inermis).